Associação dos sintomas de depressão com o consumo alimentar em mulheres climatéricas - Oldra, Caroline de Maman (2019)
Climacteric is a natural phase in woman's life, which usually occurs between the ages of 40 and 65. In this phase, the production of ovarian hormones (estrogen and progesterone) declines and eventually stops. Most women suffer from various physical and/or psychological symptoms, such as depression, impacting on their quality of life. Depression is a highly disabling, chronic, and recurrent disease that, in its more severe conditions, can lead to death. Because of this, treatment and prevention alternatives have been studied, such as the role of nutrients - such as omega-3 fatty acids - in reducing depression. Thus, the present study aimed to associate food intake and depressive symptoms in climacteric women. This is a cross-sectional study involving 400 climacteric women aged between 40 to 65 years-old, who sought gynecological or nutritional care at Basic Health Units from a municipality in southwestern Paraná (Brazil) between November 2018 and July 2019. Women in the climacteric period, who were not using hormone replacement therapy were included in the study; those who were not interested were not included in the study. Sociodemographic and clinical data were collected through interviews. Anthropometric assessment was performed by measuring weight and height. The Kupperman Menopausal Index and the Center for Epidemiologic Studies Depression Scale were used to evaluated climacteric and depression symptoms, respectively. A three-day food diary was used to assess food intake, especially omega-3's. For sample characterization, we used descriptive statistics, expressed by absolute and relative frequency; Mann-Whitney, Kruskal-Wallis, Pearson's chi-square and Hierarchical Linear Regression tests were used to verify the associations between depression with the independent variables. Statistically significant results were observed between higher depressive symptoms in women with moderate to severe climacteric symptoms, among perimenopausal women, who had a previous history of the disease and used antidepressants, with low family income and who did not sleep well. Also, a low intake of carbohydrates, fiber, polyunsaturated fatty acids, magnesium, zinc and vitamins C and D showed a statistically significant relationship with the presence of depression, while adequate consumption of vitamin B12 was observed among women with symptoms of the disease. It is noteworthy that climacteric symptoms and food consumption are important factors for the onset or even for the worsening of depression in the climacteric period. Further studies are needed to clarify the changes in this phase of women's lives, as well as to investigate the role of diet (especially omega-3) to assist depression treatment.